Trust and the Limits of Trust: A Qualitative Exploration of Healthcare Experiences among Immigrant Patients in Norway - Beret Bråten; Thea Beate Brevik (Nordisk Välfärdsforskning)
In this article, we explore and discuss how immigrant patients perceive trust in healthcare services. We ask how trust in healthcare is expressed by the patients, whether there are limits to trust, and how these limits can be interpreted. The study employs qualitative research methods – interviews with nine immigrant patients in Norway about their experiences and perceptions of healthcare services. We conducted a thematic analysis of the material. The interviewees described trust in healthcare either as a product of a reciprocal relationship with health professionals or as a requirement for coping with their illness, where they had no choice but to trust the doctor. The former perspective implies that trust is not a given, but something that can be established or lost depending on the quality of communication and interaction. The latter perspective implies that trust is a social expectation and a coping mechanism, rather than a genuine expression of confidence or satisfaction. Limits to trust are made visible when interviewees underline the importance of being informed. They are told to rely on the information they receive from health professionals. However, some also accessed alternative sources of information from the internet or their social networks. They did not disclose these practices to health professionals, possibly in order to maintain their image as rational and compliant patients and to avoid the risk of losing trust or respect. We have identified a lack of reciprocity in their relationship with professionals, and we interpret this as an important limitation to trust.